A comprehensive electric field analysis of a multifunctional electrospinning platform - Jentzsch, Erol; Gul, Omer; Oznergiz, Ertan (ELSEVIER SCIENCE BV, 2013)
The electric field is one of the most critical parameters in electrospinning process. This study provides a comprehensive electric field analysis of a multifunctional electrospinning platform performed by FEMM 4.2. In this paper firstly information about the electrospinning method is mentioned. Electric field distribution of the multifunctional electrospinning platform is analyzed in different voltage levels. The effect of the applied voltage between the needles and the collector on nanofibers is investigated which are collected on the chassis. Furthermore the analysis results clearly demonstrated the effect of electrostatic force on the multiple jets which are at the needle tips. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Electrospinning; Electric field analysis; Multifunctional electrospinning platform; FIBERS; Engineering